Cues of High and Low Body Weight Negatively Influence Adults' Perceptions and Ratings in the Hypothetical Adoption Paradigm - Anthony A. Volk; Vernon l. Quinsey (The Scientific World Journal)
Infant and child facial cues influence perceptions and ratings in the Hypothetical Adoption Paradigm as well as actual parental care. A previous study demonstrated that infant and child facial cues of low body weight negatively influenced adults' ratings. The current study sought to replicate and expand on those results by presenting adults with normal faces as well as faces that were digitally altered to display high or low body weight. Cues of abnormal body weight significantly, and negatively, influenced adults ratings of adoption preference, health, and cuteness. Effect sizes were larger for cues of high body weight. Thus, infant and child facial cues of abnormal body weight may represent a relative risk factor to the quality of adult care obtained by children with abnormal body weight.